Econometric Determinants of Chinese Developmental Finance in Sub-Saharan Africa; Further Evidence Using a Flow-Type Decomposed Poisson Pseudo-Maximum Likelihood Model (Global Journal of Human-Social Science, 2024)
Abstract not found
Keywords: developmental finance; concessionality; econometrics; zero-inflation; poisson pseudo-maximum likelihood (PPML)